Anti-oil-spitting UV (ultraviolet) transparent primer as well as preparation process and test method thereof
By using resin combinations such as hyperbranched polyester acrylate in UV transparent primer, the existing UV transparent primer lacks adhesion and easy bubbles during construction of wood surfaces, and a coating with high adhesion and good anti-oil spray performance on natural pine substrates is achieved, which extends the service life and improves the physical and chemical properties of the paint film.
Patent Information
- Application Number
- CN202411930020.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-11
AI Technical Summary
The existing UV transparent primer is prone to insufficient adhesion, blistering, bleaching and falling off at scars and short storage time when constructing the wood surface, especially on natural pine substrates.
Hyperbranched polyester acrylate is used as the main resin, combined with 3-functional polyurethane acrylate resin and a special modified acrylate adhesion resin, and by adjusting the optimal ratio between each oligomer, a UV transparent primer with high adhesion and anti-oil spray performance is formed.
It realizes a coating with high adhesion and good anti-oil spray performance on natural pine substrates, extends service life, improves the physical and chemical properties and aesthetics of the paint film, and reduces terminal production costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to an anti-oil spitting UV transparent primer and a preparation process and a testing method thereof. Background Art
[0002] In recent years, the real estate market has been sluggish, and the market size of wood paint has shrunk accordingly, and competition has intensified. End customers have continuously improved their quality requirements for wood paint products, and have put forward higher standards for product construction tolerance, construction parameters, physical and chemical properties of paint films, and cost performance. Existing UV transparent primers generally have problems such as lack of adhesion, easy blistering, easy whitening and falling off of scars, and short storage time, which seriously affect the construction effect and service life of the product.
[0003] Existing UV transparent primers are mainly applied to smooth wooden surfaces, and are highly sensitive to the roughness and moisture of wood. During the application process, bubbles and paint leaks are likely to occur, affecting the final paint film effect. In addition, for woods containing rosin, such as pine, existing UV transparent primers are difficult to effectively inhibit the volatilization of rosin, resulting in easy bubbling of the paint film, and easy whitening and falling off of the scars, showing poor aesthetics. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-oil spitting UV transparent primer and its preparation process and testing method, which are specifically aimed at the natural pine wood substrate in the school equipment market, and solve the problems of common UV transparent primers in the current market, such as no adhesion, easy bubbling of the paint film, easy whitening and falling off of the scars, short storage time, etc. At the same time, it also meets the practical problems raised by users on the product, such as tolerance, physical and chemical properties of the paint film, etc.
[0005] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0006] An anti-oil spitting UV transparent primer comprises the following components in parts by weight:
[0007]
[0008] Preferably, the hyperbranched polyester acrylate is YTM9800 produced by Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd.;
[0009] The trifunctional polyurethane acrylate resin is YTM4300 produced by Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd.
[0010] The special modified acrylic adhesion resin adopts YTM3000 produced by Guangdong Nippon Changrunfa Technology Materials Co., Ltd.;
[0011] The trimethylolpropane triacrylate is trimethylolpropane triacrylate YTM6350 produced by Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd.
[0012] Preferably, the zinc stearate is Dongguan Hanwei TV-P, the talc powder (SiO2 content is 10-50%) is Guangdong Housheng 1250 mesh talc powder; the dispersant is BYK-20084; the defoamer is AFCONA 2270; and the acrylate leveling agent is BYK-358N.
[0013] Preferably, the fumed silica is Cabot CAB-O-SIL M-5, the bentonite is BYK GARAMITE-1958, and the liquid rheological agent is German BYK BYK-410.
[0014] Preferably, the 2-hydroxy-2-methyl-1-phenyl-1-propanone is Tianjin Jiuri 1103, and the bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is Tianjin Jiuri 1109.
[0015] A preparation process of an anti-oil spitting UV transparent primer, which is applied to any of the above-mentioned anti-oil spitting UV transparent primers, comprises the following steps:
[0016] S1: Select the production cylinder, confirm that the inner wall of the cylinder has been cleaned and the discharge valve is closed;
[0017] S2: Add hyperbranched polyester acrylate, trifunctional polyurethane acrylate resin and special modified acrylate adhesion resin into the production tank, and disperse them at medium speed in a disperser for 5-10 minutes;
[0018] S3: Add dispersant and defoamer into the production tank and disperse at medium speed for 5-10 minutes;
[0019] S4: Add meteorological silica, bentonite, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone and zinc stearate into the production tank, and disperse at high speed for 25-30 minutes using a disperser;
[0020] S5: Add acrylate leveling agent, liquid rheological agent and trimethylolpropane triacrylate into the production cylinder and disperse them at medium speed in a disperser for 10-15 minutes.
[0021] Preferably, the high-speed dispersing speed of the disperser is 1500±200 rpm; the medium-speed dispersing speed of the disperser is 1000±200 rpm; and the low-speed dispersing speed of the disperser is 500±100 rpm.
[0022] A testing method for an anti-oil-spitting UV transparent primer is applied to any of the above-mentioned anti-oil-spitting UV transparent primers, comprising the following steps: selecting a natural pinewood substrate → lightly polishing → roller-coating the anti-oil-spitting UV primer → first UV mercury lamp curing and drying → 320# sandpaper sanding → roller-coating the UV transparent primer → second UV mercury lamp curing and drying → 320#+400# sandpaper sanding → UV laser roller coating of matte clear topcoat → third UV mercury lamp curing and drying, and testing various properties after the board temperature drops to room temperature.
[0023] Preferably, the roller-coated anti-oil spitting UV primer has a coating amount of 25-35 g / m 2 The roller-coated UV transparent primer has a coating amount of 20-40g / m 2 The UV laser roller coating matte clear topcoat has a coating amount of 20-40g / m 2 .
[0024] Preferably, the first UV curing with mercury lamp is completely dry, and the energy is 100-200mJ / cm 2 The second UV mercury lamp curing is completely dry, with an energy of 200-300mJ / cm 2 The third UV mercury lamp curing is completely dry, with an energy of 200-300mJ / cm 2 .
[0025] The anti-oil spitting UV transparent primer and its preparation process and testing method have the following beneficial effects:
[0026] 1. The anti-oil spitting UV transparent primer of the present invention uses hyperbranched polyester acrylate as the main resin, and is matched with tri-functional polyurethane acrylate resin and special modified acrylate adhesion resin to form the main components, so that the main resin has the characteristics of fast curing speed, small curing shrinkage, environmental protection, high hardness, good toughness, good adhesion, good yellowing resistance, good weather resistance, etc.;
[0027] 2. The anti-oil spitting UV transparent primer of the present invention uses hyperbranched polyester acrylate as the main resin, and is matched with trifunctional polyurethane acrylate resin and special modified acrylate adhesion resin to form the main components, and is further matched with trimethylolpropane triacrylate as an active diluent, so that it has good adhesion to the pine wood substrate, can effectively form a strong coating, and prolongs the service life. The raw materials do not contain heavy metals and halogens, and the product is environmentally friendly and safe.
[0028] 3. The anti-oil spitting UV transparent primer of the present invention has excellent anti-oil spitting performance by adjusting the optimal ratio between the oligomers, effectively preventing the oil seepage of wood, keeping the paint film clear and stable, and avoiding oil stain pollution and defects;
[0029] 4. The anti-oil spitting UV transparent primer of the present invention has high construction efficiency, fast system curing efficiency, relatively lower terminal production cost and good storage stability by testing and screening the system compatibility between the main resin and the active diluent and the auxiliary filler. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0031] It should be noted that all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0032] An anti-oil spitting UV transparent primer comprises the following components in parts by weight: 20-50 parts of hyperbranched polyester acrylate, 5-20 parts of trifunctional polyurethane acrylate resin, 5-20 parts of special modified acrylate adhesion resin, 0.5-1 parts of dispersant, 0.1-0.3 parts of defoamer, 0.1-0.3 parts of meteorological silica, 0.1-0.2 parts of bentonite, 0.2-0.3 parts of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 3-4 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-2 parts of zinc stearate, 0.2-0.3 parts of acrylate leveling agent, 0.1-0.3 parts of liquid rheological agent and 5-15 parts of trimethylolpropane triacrylate.
[0033] It should be noted that: the hyperbranched polyester acrylate adopts 8-official hyperbranched polyester acrylate, which has the characteristics of fast curing speed, small curing shrinkage, environmental protection, high hardness, etc. It is used as the main resin, matched with 3-official polyurethane acrylate resin and special modified acrylate adhesion resin. The 3-official polyurethane acrylate resin has the characteristics of good toughness, low shrinkage, good adhesion, good yellowing resistance, good weather resistance, etc. The special modified acrylate adhesion resin has the characteristics of providing wettability, balancing internal stress, and enhancing adhesion effect. The trimethylolpropane triacrylate is used as an active diluent. The agent is matched with the main resin to effectively improve the conversion rate and curing speed; the dispersant uses an acrylic copolymer solution to improve the overall wettability of the system so that the coating can be spread more evenly on the surface of the substrate; the liquid rheological agent is used as an anti-settling agent; the 2-hydroxy-2-methyl-1-phenyl-1-propanone and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide can balance the deep and surface curing efficiency; the zinc stearate is used as an organic matter, and the talc is used as a magnesium silicate mineral. The SiO2 content used is 10-50%, which can solve the problem of difficult sanding.
[0034] The hyperbranched polyester acrylate adopts YTM9800 from Guangdong Nippon Changrunfa Technology Materials Co., Ltd.; the tri-functional polyurethane acrylate resin adopts YTM4300 from Guangdong Nippon Changrunfa Technology Materials Co., Ltd.; the special modified acrylate adhesion resin adopts YTM3000 from Guangdong Nippon Changrunfa Technology Materials Co., Ltd.; the trimethylolpropane triacrylate adopts trimethylolpropane triacrylate YTM6350 from Guangdong Nippon Changrunfa Technology Materials Co., Ltd. The zinc stearate adopts Dongguan Hanwei TV-P, the talc powder (SiO2 content is 10-50%) adopts Guangdong Housheng 1250 mesh talc powder; the dispersant adopts BYK-20084; the defoamer adopts AFCONA 2270; the acrylate leveling agent adopts BYK-358N. The meteorological silica is Cabot CAB-O-SIL M-5, the bentonite is BYK GARAMITE-1958, the liquid rheological agent is BYK-410 from Germany, the 2-hydroxy-2-methyl-1-phenyl-1-propanone is Tianjin Jiuri 1103, and the bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is Tianjin Jiuri 1109.
[0035] It should be noted that the main resin uses Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd. YTM9800 hyperbranched polyester acrylate, Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd. YTM4300 tri-functional polyurethane acrylate resin and a small amount of Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd. YTM3000 special modified acrylate adhesion resin to meet the requirements of wettability, curing speed, drying, adhesion and cost performance. The monomer uses high-purity Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd. trimethylolpropane triacrylate YTM6350, which has high functional groups, high conversion rate with the main resin and fast curing speed.
[0036] A preparation process of an anti-oil spitting UV transparent primer is used to prepare the above-mentioned anti-oil spitting UV transparent primer. The specific material components and their corresponding weights are shown in Table 1, and the primer is prepared by the following steps:
[0037] S1: Select the production cylinder, confirm that the inner wall of the cylinder has been cleaned and the discharge valve is closed;
[0038] S2: Add hyperbranched polyester acrylate, trifunctional polyurethane acrylate resin and special modified acrylate adhesion resin into the production tank, and disperse the mixture at a medium speed of 1000±200 rpm for 5-10 minutes.
[0039] S3: Add dispersant and defoamer into the production tank, the medium speed dispersing speed of the disperser is 1000±200 rpm, and the dispersion time is 5-10 minutes;
[0040] S4: Add meteorological silica, bentonite, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone and zinc stearate into the production tank, and disperse the mixture at a high speed of 1500±200 rpm for 25-30 minutes.
[0041] S5: Add acrylate leveling agent, liquid rheological agent and trimethylolpropane triacrylate into the production cylinder, and disperse the mixture at a medium speed of 1000±200 rpm for 10-15 minutes.
[0042] The following table shows the components and weight compositions of the anti-oil spitting UV transparent primer in Examples 1-6:
[0043]
[0044]
[0045] Performance Testing
[0046] The anti-oil spitting UV transparent primers prepared in Examples 1-6 were tested using the following method. The test results are recorded in Table 2.
[0047] A test method for an anti-oil spitting UV transparent primer, which is applied to the anti-oil spitting UV transparent primer, comprises the following steps: selecting a natural pine wood substrate → lightly throwing → roller coating the anti-oil spitting UV primer, with a construction coating amount of 25-35g / m 2 →The first UV mercury lamp curing is completely dry, the energy is 100-200mJ / cm 2 → Sanding with 320# sandpaper → Roller-coated UV transparent primer, with a coating amount of 20-40g / m 2 → The second UV mercury lamp curing is completely dry, the energy is 200-300mJ / cm 2 →320#+400# sandpaper sanding →UV laser roller coating matte clear topcoat, construction coating amount 20-40g / m 2 →The third UV mercury lamp curing is completely dry, the energy is 200-300mJ / cm 2 , and then test various properties after the board temperature drops to room temperature.
[0048] The paint and paint film of the present invention were tested and evaluated according to HG / T 3655-2012. The performance results corresponding to different resin ratios in Comparative Examples 1-6 are shown in Table 2:
[0049]
[0050]
[0051] In the above test examples, Example 5 has the best comprehensive performance. When the proportion of hyperbranched resin is ≥45%, the overall paint film is brittle and easy to collapse. When the proportion is lower than 25%, the anti-oil spitting and anti-whitening properties are significantly reduced.
[0052] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the specification and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention still belong to the present invention.
Claims
1. An anti-oil spitting UV transparent primer, characterized by: The composition includes the following components by weight:
2. The anti-oil spitting UV transparent primer according to claim 1, characterized in that: The hyperbranched polyester acrylate is YTM9800 produced by Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd. The trifunctional polyurethane acrylate resin is YTM4300 produced by Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd. The special modified acrylic adhesion resin adopts YTM3000 produced by Guangdong Nippon Changrunfa Technology Materials Co., Ltd.; The trimethylolpropane triacrylate is trimethylolpropane triacrylate YTM6350 produced by Guangdong Nippon Paint Changrunfa Technology Materials Co., Ltd.
3. The anti-oil spitting UV transparent primer according to claim 1, characterized in that: The zinc stearate is Dongguan Hanwei TV-P, the talc powder (SiO2 content is 10-50%) is Guangdong Housheng 1250 mesh talc powder; the dispersant is BYK-20084; the defoamer is AFCONA 2270; and the acrylic leveling agent is BYK-358N.
4. The anti-oil spitting UV transparent primer according to claim 1, characterized in that: The meteorological silica is Cabot CAB-O-SIL M-5, the bentonite is BYK GARAMITE-1958, and the liquid rheological agent is German BYK-410.
5. The anti-oil spitting UV transparent primer according to claim 1, characterized in that: The 2-hydroxy-2-methyl-1-phenyl-1-propanone is made of Tianjin Jiuri 1103, and the bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is made of Tianjin Jiuri 1109.
6. A preparation process of an anti-oil spitting UV transparent primer, characterized in that: The anti-oil spitting UV transparent primer used in any one of claims 1 to 5 comprises the following steps: S1: Select the production cylinder, confirm that the inner wall of the cylinder has been cleaned and the discharge valve is closed; S2: Add hyperbranched polyester acrylate, trifunctional polyurethane acrylate resin and special modified acrylate adhesion resin into the production tank, and disperse them at medium speed in a disperser for 5-10 minutes; S3: Add dispersant and defoamer into the production tank and disperse at medium speed for 5-10 minutes; S4: Add meteorological silica, bentonite, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone and zinc stearate into the production tank, and disperse at high speed for 25-30 minutes using a disperser; S5: Add acrylate leveling agent, liquid rheological agent and trimethylolpropane triacrylate into the production cylinder and disperse them at medium speed in a disperser for 10-15 minutes.
7. The preparation process of the anti-oil spitting UV transparent primer according to claim 6, characterized in that: The high-speed dispersing speed of the dispersing machine is 1500±200 rpm; the medium-speed dispersing speed of the dispersing machine is 1000±200 rpm; and the low-speed dispersing speed of the dispersing machine is 500±100 rpm.
8. A testing method for anti-oil spitting UV transparent primer, characterized in that: The anti-oil spitting UV transparent primer used in any one of claims 1 to 5 comprises the following steps: selecting a natural pine wood substrate → lightly polishing → roller-coating the anti-oil spitting UV primer → first UV mercury gallium lamp curing and drying → 320# sandpaper sanding → roller-coating the UV transparent primer → second UV mercury gallium lamp curing and drying → 320#+400# sandpaper sanding → UV laser roller coating of matte clear topcoat → third UV mercury gallium lamp curing and drying, and testing various properties after the board temperature drops to room temperature.
9. The testing method of the anti-oil spitting UV transparent primer according to claim 8, characterized in that: The roller-coated anti-oil spitting UV primer has a coating amount of 25-35g / m 2 The roller-coated UV transparent primer has a coating amount of 20-40g / m 2 The UV laser roller coating matte clear topcoat has a coating amount of 20-40g / m 2 .
10. The testing method of the anti-oil spitting UV transparent primer according to claim 8, characterized in that: The first UV curing with mercury lamp is completely dry, and the energy is 100-200mJ / cm 2 ; The second UV curing with mercury lamp is completely dry, and the energy is 200-300mJ / cm 2 ; The third UV mercury lamp curing is completely dry, and the energy is 200-300mJ / cm 2 .
Citation Information
Patent Citations
UV-curing primer for marble
CN104530931A
Ultra-wear-resistant UV light curing release coating and preparation method thereof
CN109337532A
UV primer-topcoat integrated paint for 3D printing plate and preparation method of UV primer-topcoat integrated paint
CN115651500A
Special UV roller coating adhesion primer for scar pine oil and preparation method of special UV roller coating adhesion primer
CN115710452A
UV mercury lamp light source cured pine oil sealing primer and preparation method thereof
CN115960500A